The Effect of Tourists’ Experience Towards Revisit Intention at Perkampungan Budaya Betawi Setu Babakan - Rahmat Ingkadijaya; Linda Desafitri RB; Poppy Wira Pertiwi (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2021)
Perkampungan Budaya Betawi Area is cultural preservation designated by the Jakarta government as a location for the preservation and development of Betawi culture. As one of the cultural tourism destinations in the center of the Capital that always strives to maintain and improve all important aspects that have an impact on the sustainability of the tourist destination itself. The Tourists mostly come from West Java, Jabodetabek, and Foreign. Therefore, the authors conducted a pre-study on tourists’ revisit intention of Perkampungan Budaya Betawi Setu Babakan which produces that tourists revisit intention is low. Implementing the customer experience to be expected could increase the revisit intention to Perkampungan Budaya Betawi Setu Babakan. This type of research was descriptive quantitative, the survey method used was the questioner with a sample size of 100 respondents. Data analysis technique was using the multiple regression techniques. These results show there is a partial influence on customer experience consisting of comfort, education, hedonic, novelty, safety, and beauty to tourists’ revisit intention of Perkampungan Budaya Betawi Setu Babakan. The beauty dimension of the customer experience variable got the highest score and the intention to recommend in revisit intention got the highest score